2013
DOI: 10.1590/s0103-51502013000400015
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas musculoesqueléticos em motoristas de ônibus: prevalência e fatores associados

Abstract: INTRODUÇÃO: Os profissionais do transporte coletivo realizam atividades laborais que envolvem grande número de fatores de risco para acometimentos musculoesqueléticos, e o conhecimento desses riscos é fundamental para que esses trabalhadores possam gozar de boa qualidade de vida. OBJETIVOS: Verificar a prevalência dos sintomas musculoesqueléticos em motoristas de ônibus urbano e investigar fatores associados. MATERIAIS E MÉTODOS: Realizou-se um estudo transversal com 55 motoristas de uma empresa de uma cidade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
3
0
9
Order By: Relevance
“…This shows that sedentary workers are more likely to feel pain. This is in line with a study conducted among bus drivers, in which 28.0% were more likely to feel pain because they did not practice physical exercises (14) . It was shown that 45.5% of agents who need medical care and 56.1% of those who need psychological care reported feeling strong/unbearable musculoskeletal pain.…”
Section: Discussionsupporting
confidence: 91%
“…This shows that sedentary workers are more likely to feel pain. This is in line with a study conducted among bus drivers, in which 28.0% were more likely to feel pain because they did not practice physical exercises (14) . It was shown that 45.5% of agents who need medical care and 56.1% of those who need psychological care reported feeling strong/unbearable musculoskeletal pain.…”
Section: Discussionsupporting
confidence: 91%
“…As regiões corporais que apresentaram maior prevalência de lesões osteomusculares foram ao longo da região do esqueleto axial, principalmente com prevalência de dor na parte superior das costas 10 , ombros 5,7,11,12 , pescoço 5,7 , braços e mãos 5 , região lombar 7,8,12 , membros inferiores, tais como joelhos 7,12 .…”
Section: Discussionunclassified
“…Estudos apontaram que certas posturas adotadas pelos motoristas de ônibus, podem favorecer o aparecimento de dores, sendo a dor na região lombar como a mais desenvolvida 8,9,12 . É relatado que 81,9% dos motoristas de ônibus experimentam dores na região lombar e estão intimamente relacionadas às condições de trabalho e à vibração de corpo inteiro recebida do veículo e da estrada.…”
Section: Discussionunclassified
“…In relation to the age group, results are similar to the ones found in the study of Coury et al 10 , evaluating women from Paraná, Brazil, also workers of textile industries. According to Vitta et al 11 , the low level of education forms a specific group of employees, which starts working early, reflecting in less specialized professions (seamstresses, mechanic, bus driver etc. ), exposed to many ergonomic risk factors such as: repetition, strength, vibration, bad posture, among others.…”
Section: Discussionmentioning
confidence: 99%